2017
DOI: 10.1038/cddis.2017.275
|View full text |Cite
|
Sign up to set email alerts
|

Titanium particle-induced osteogenic inhibition and bone destruction are mediated by the GSK-3β/β-catenin signal pathway

Abstract: Wear debris-induced osteogenic inhibition and bone destruction are critical in the initiation of peri-prosthetic osteolysis. However, the molecular mechanism underlying this phenomenon is poorly understood. In this study, we analyzed the involvement of the GSK-3β/β-catenin signal pathway, which is important for bone formation in this pathological condition. We established a titanium (Ti) particle-stressed murine MC3T3-E1 cell culture system and calvariae osteolysis model to test the hypothesis that Ti particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
(53 reference statements)
2
37
0
Order By: Relevance
“…It was highly expressed in the AS group and was also decreased after metformin administration, indicated that metformin may suppress the osteogenesis of fibroblasts in AS. Our results indicated that metformin also decreased the ALP positive staining, activity, and mRNA expression (one of the early osteogenic markers) in fibroblasts, which confirmed the phenomenon above. Besides, Bglap, also known as osteocalcin (Ocn), is a key factor to calcium deposition, was significantly decreased by metformin intervention, especially for AS fibroblasts.…”
Section: Discussionsupporting
confidence: 88%
“…It was highly expressed in the AS group and was also decreased after metformin administration, indicated that metformin may suppress the osteogenesis of fibroblasts in AS. Our results indicated that metformin also decreased the ALP positive staining, activity, and mRNA expression (one of the early osteogenic markers) in fibroblasts, which confirmed the phenomenon above. Besides, Bglap, also known as osteocalcin (Ocn), is a key factor to calcium deposition, was significantly decreased by metformin intervention, especially for AS fibroblasts.…”
Section: Discussionsupporting
confidence: 88%
“…Research showed this pathway played a role in the development of osteolytic disease [30]. The importance of regulation of the Wnt/β-catenin signaling pathway has also been noted in the eld of aseptic loosening research [31,33]. β-catenin is an important part of Wnt/β-catenin signaling, which modulates transcription of Wnt target genes, including OPG [34].…”
Section: Discussionmentioning
confidence: 99%
“…GSK has been shown to modulate many transcription factors, such as AP-1, CREB, and b-catenin (29)(30)(31)(32)(33)(34). AP-1 acts as a transcription factor that regulates cell proliferation, survival, and apoptosis (35).…”
Section: Discussionmentioning
confidence: 99%